Short-Term Blood Pressure Variability Relates to the Presence of Subclinical Brain Small Vessel Disease in Primary Hypertension - Filomena, Josefina; Riba-Llena, Iolanda; Vinyoles, Ernest; Tovar, José L.; Mundet, Xavier; Castañé, Xavier; Vilar, Andrea; López-Rueda, Antonio; Jiménez-Baladó, Joan; Cartanyà, Anna; Montaner, Joan; Delgado, Pilar (Hypertension (Dallas, Tex. 1979), 2015)
Blood pressure (BP) variability is associated with stroke risk, but less is known about subclinical cerebral small vessel disease (CSVD). We aimed to determine whether CSVD relates to short-term BP variability independently of BP levels and also, whether they improve CSVD discrimination beyond clinical variables and office BP levels. This was a cohort study on asymptomatic hypertensives who underwent brain magnetic resonance imaging and 24-hour ambulatory BP monitoring. Office and average 24-hour, daytime and nighttime BP levels, and several metrics of BP variability (SD, weighted SD, coefficient of variation, and average real variability [ARV]) were calculated. Definition of CSVD was based on the presence of lacunar infarcts and white matter hyperintensity grades. Multivariate analysis and integrated discrimination improvement were performed to assess whether BP variability and levels were independently associated with CSVD and improved its discrimination. Four hundred eighty-seven individuals participated (median age, 64; 47% women). CSVD was identified in 18.9%, related to age, male sex, diabetes mellitus, use of treatment, ambulatory BP monitoring–defined BP levels, and ARV of systolic BP at any period. The highest prevalence (33.7%) was found in subjects with both 24-hour BP levels and ARV elevated. BP levels at any period and ARV (24 hours and nocturnal) emerged as independent predictors of CSVD, and discrimination was incrementally improved although not to a clinically significant extent (integrated discrimination improvement, 5.31%, 5.17% to 5.4%). Ambulatory BP monitoring–defined BP levels and ARV of systolic BP relate to subclinical CSVD in hypertensive individuals.